O ideário pedagógico das competências na Base Nacional Comum Curricular: contraposições à luz da Pedagogia Histórico-Crítica - Souza, Lorena Chrystinne Borges de (Brasil, 2025)
The aim of this study was to analyze the consequences for the development of human psyche of a canonical curriculum designed to promote human adaptation to the economic structures of society, through an educational system model and background based on the Pedagogy of Competencies, as outlined in the Brazilian curricular document, the Base Nacional Comum Curricular (BNCC). This study is grounded in historical-dialectical materialism, seeking to contextualize the confrontation between the forces of the political-economic field that led to the emergence of the BNCC, and to analyze, through historical-cultural psychology, its consequences for human development. The study proposes the possibility of constructing an omnilateral formation of the human being, based on the goals of Historical-Critical Pedagogy. To investigate the object of analysis, the study relies on a literature review and documentary analysis. The results indicate the need for a revision of this curricular model, as we understand, based on the analysis presented, its pragmatic character, which entails setbacks to omnilateral development. In contrast, the pathways proposed by Historical-Critical Pedagogy suggest a curriculum that enables the acquisition of philosophical, artistic, and scientific knowledge for the full development of the human being and their critical and transformative consciousness.